Check the picture below.
and since a triangle has a sum of 180° for all interior angles.
A = 180 - 39.34 - 25
A = 115.66
![\bf \cfrac{sin(25^o)}{44}=\cfrac{sin(A)}{a}\implies \cfrac{sin(25^o)}{44}=\cfrac{sin(115.66^o)}{a} \\\\\\ a\cdot sin(25^o)=44\cdot sin(115.66^o)\implies a=\cfrac{44\cdot sin(115.66^o)}{sin(25^o)} \\\\\\ a\approx 93.8452\implies \stackrel{\textit{rounded up}}{a = 93.85}](https://tex.z-dn.net/?f=%5Cbf%20%5Ccfrac%7Bsin%2825%5Eo%29%7D%7B44%7D%3D%5Ccfrac%7Bsin%28A%29%7D%7Ba%7D%5Cimplies%20%5Ccfrac%7Bsin%2825%5Eo%29%7D%7B44%7D%3D%5Ccfrac%7Bsin%28115.66%5Eo%29%7D%7Ba%7D%20%5C%5C%5C%5C%5C%5C%20a%5Ccdot%20sin%2825%5Eo%29%3D44%5Ccdot%20sin%28115.66%5Eo%29%5Cimplies%20a%3D%5Ccfrac%7B44%5Ccdot%20sin%28115.66%5Eo%29%7D%7Bsin%2825%5Eo%29%7D%20%5C%5C%5C%5C%5C%5C%20a%5Capprox%2093.8452%5Cimplies%20%5Cstackrel%7B%5Ctextit%7Brounded%20up%7D%7D%7Ba%20%3D%2093.85%7D)
make sure your calculator is in Degree mode.
V of rectangular prism = l * w * h = 12 * 2 * 312 = 7,488 in³
V of one cube with side lengths 12 = l * w * h = 12 * 12 * 12 = 1,728 in³
Divide the volume of rectangular prism by the volume of the cube.
7488 / 1728 = 13 / 3 or 4.3. . .
Answer: 144 inches.
Step-by-step explanation:
1. To solve this problem you must remember the formula for calculate the perimeter of a rectangle, which is shown below:
![P=2l+2w](https://tex.z-dn.net/?f=P%3D2l%2B2w)
Where
is the lenght and
is the width.
2. You know the perimeter and the width, then you can solve for the length, as following:
![P-2w=2l\\l=\frac{P-2w}{2}\\l=\frac{(528in)-(2*120in))}{2}\\l=144in](https://tex.z-dn.net/?f=P-2w%3D2l%5C%5Cl%3D%5Cfrac%7BP-2w%7D%7B2%7D%5C%5Cl%3D%5Cfrac%7B%28528in%29-%282%2A120in%29%29%7D%7B2%7D%5C%5Cl%3D144in)
Answer:
![\large\boxed{5x-6y=16}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B5x-6y%3D16%7D)
Step-by-step explanation:
The standard form of an equation of a line:
![Ax+By=C](https://tex.z-dn.net/?f=Ax%2BBy%3DC)
We have the equation in the point-slope form. Convert:
![y+1=\dfrac{5}{6}(x-2)\qquad\text{multiply both sides by 6}\\\\6y+6=6\!\!\!\!\diagup^1\cdot\dfrac{5}{6\!\!\!\!\diagup_1}(x-2)\\\\6y+6=5(x-2)\qquad\text{use the distributive property}\\\\6y+6=(5)(x)+(5)(-2)\\\\6y+6=5x-10\qquad\text{subtract 6 from both sides}\\\\6y+6-6=5x-10-6\\\\6y=5x-16\qquad\text{subtract}\ 5x\ \text{from both sides}\\\\-5x+6y=5x-5x-16\\\\-5x+6y=-16\qquad\text{change the signs}\\\\\boxed{5x-6y=16}](https://tex.z-dn.net/?f=y%2B1%3D%5Cdfrac%7B5%7D%7B6%7D%28x-2%29%5Cqquad%5Ctext%7Bmultiply%20both%20sides%20by%206%7D%5C%5C%5C%5C6y%2B6%3D6%5C%21%5C%21%5C%21%5C%21%5Cdiagup%5E1%5Ccdot%5Cdfrac%7B5%7D%7B6%5C%21%5C%21%5C%21%5C%21%5Cdiagup_1%7D%28x-2%29%5C%5C%5C%5C6y%2B6%3D5%28x-2%29%5Cqquad%5Ctext%7Buse%20the%20distributive%20property%7D%5C%5C%5C%5C6y%2B6%3D%285%29%28x%29%2B%285%29%28-2%29%5C%5C%5C%5C6y%2B6%3D5x-10%5Cqquad%5Ctext%7Bsubtract%206%20from%20both%20sides%7D%5C%5C%5C%5C6y%2B6-6%3D5x-10-6%5C%5C%5C%5C6y%3D5x-16%5Cqquad%5Ctext%7Bsubtract%7D%5C%205x%5C%20%5Ctext%7Bfrom%20both%20sides%7D%5C%5C%5C%5C-5x%2B6y%3D5x-5x-16%5C%5C%5C%5C-5x%2B6y%3D-16%5Cqquad%5Ctext%7Bchange%20the%20signs%7D%5C%5C%5C%5C%5Cboxed%7B5x-6y%3D16%7D)
Answer:
C
Step-by-step explanation: